Extraction of rare earth elements using magnetite@MOF composites. Issue 38 (24th September 2018) - Elsaidi, Sameh K.; Sinnwell, Michael A.; Devaraj, Arun; Droubay, Tim C.; Nie, Zimin; Murugesan, Vijayakumar; McGrail, B. Peter; Thallapally, Praveen K.
Abstract : Magnetic core–shell microspheres were developed to extract rare earth elements (REEs) from aqueous and brine solutions with up to 99.99% removal efficiency. The shell, composed of a thermally and chemically stable functionalized metal–organic framework (MOF), is grown over a synthesized Fe3 O4 magnetic core (magnetite@MOF). Abstract : Magnetic core–shell microspheres were developed to extract rare earth elements (REEs) from aqueous and brine solutions with up to 99.99% removal efficiency. The shell, composed of a thermally and chemically stable functionalized metal–organic framework (MOF), is grown over a synthesized Fe3 O4 magnetic core (magnetite@MOF). The composite particles can be removed from the mixture under an applied magnetic field, offering a practical, and efficient REE-removal process.